Avaliação da morfologia condilar em pacientes classe II submetidos à cirurgia ortognática - Marques, Késia Lara dos Santos (2014)
The orthognathic surgery is indicated for correction of severe skeletal disharmonies. Changes in condylar morphology after this surgery are more frequent in class II deformities associated with condylar hypoplasia. The aim of this study was to evaluate linear, angular, and volumetric changes in condylar morphology after orthognathic surgery with counterclockwise rotation of the maxillomandibular complex, from cone -beam CT scans pre and post-surgical, obtained with patients positioned with the Frankfurt plane parallel to floor. The CT images of 23 Class II patients operated on between the years 2011 and 2012 were converted into DICOM file (Digital Imagining and Communications in Medicine) and exported to the Dolphin Imaging® software for analysis two and three-dimensional in the coronal and sagittal planes. Statistical analysis of Shapiro-Wilk normality test, which defined the Student t test for normally distributed variables (P > .05) and the Wilcoxon test for variables not normally distributed (P < .05). The study showed statistically significant differences between preoperative and postoperative time to the variables: height to the articular fossa of the right condyle (right X2), posterior distance from the right condyle to articular fossa in the sagittal plane (right PS), upper distance from the right condyle to articular fossa (right SS) and anterior distance from the left condyle to the articular fossa in the sagittal plane (left AS). The variables for the analysis of 2D surface area and 3D volume showed no statistically significant differences between pre -and postoperatively. Some patients in this study had healthy temporomandibular joints (TMJ), others had disc displacement and good function. It was concluded this surgical technique is safe and clinically stable and that the results observed in this study suggest a trend for condylar remodeling, physiological and adaptive, with apposition bone in some regions and bone resorption in others, changing the morphology of the condyle and in their spatial position in the articular fossa for this surgical technique with counterclockwise rotation of the maxillomandibular complex and mandibular advancement. There is need for further studies to clarify this hypothesis scientifically.